2012
DOI: 10.1016/j.is.2012.01.004
|View full text |Cite
|
Sign up to set email alerts
|

On the refactoring of activity labels in business process models

Abstract: Large corporations increasingly utilize business process models for documenting and redesigning their operations. The extent of such modeling initiatives with several hundred models and dozens of often hardly trained modelers calls for automated quality assurance. While formal properties of control flow can easily be checked by existing tools, there is a notable gap for checking the quality of the textual content of models, in particular, its activity labels. In this paper, we address the problem of activity l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
80
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 88 publications
(83 citation statements)
references
References 59 publications
(96 reference statements)
0
80
0
2
Order By: Relevance
“…Therefore, it has been found difficult to use standard natural language processing tools like the Stanford parser. The approach reported in [54] uses different contextual information to map a label that, for instance, starts with the word plan to its correct labeling style. Once the labeling style is known, tools like WordNet can be used to find a verb that matches an action that was formulated as a noun (see Figure 3).…”
Section: Refactoring Text Labels Of Process Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it has been found difficult to use standard natural language processing tools like the Stanford parser. The approach reported in [54] uses different contextual information to map a label that, for instance, starts with the word plan to its correct labeling style. Once the labeling style is known, tools like WordNet can be used to find a verb that matches an action that was formulated as a noun (see Figure 3).…”
Section: Refactoring Text Labels Of Process Modelsmentioning
confidence: 99%
“…Once the labeling style is known, tools like WordNet can be used to find a verb that matches an action that was formulated as a noun (see Figure 3). It has been shown that this approach works accurately for three different modeling collections from practice including altogether more than 10,000 activity labels [54].…”
Section: Refactoring Text Labels Of Process Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this component, we use the linguistic label analysis technique from [21] to recognize the different label patterns that exist for activity labels in the process view. In this way, for instance, we are able to decompose an activity label such as Choose Contact Type into the action Choose and the business object Contact Type.…”
Section: Linguistic Information Extractionmentioning
confidence: 99%
“…Nevertheless, prior research highlighted the challenges that are associated with the automatic analysis of natural language in process models [2]. Since process model labels do not contain full and grammatically correct sentences, the application of standard tools for natural language processing such as parsers turned out to be hardly possible.…”
Section: Introductionmentioning
confidence: 99%